Rethinking global health research: towards integrative expertise - MacLachlan Malcolm (BMC, 2009)
Abstract The Bamako Call for Action on Research for Health stresses the importance of inter-disciplinary, inter-ministerial and inter-sectoral working. This challenges much of our current research and postgraduate research training in health, which mostly seeks to produce narrowly focused content specialists. We now need to compliment this type of research and research training, by offering alternative pathways that seek to create expertise, not only in specific narrow content areas, but also in the process and context of research, as well as in the interaction of these different facets of knowledge. Such an approach, developing 'integrative expertise', could greatly facilitate better research utilisation, helping policy makers and practitioners work through more evidence-based practice and across traditional research boundaries.